Determinants of Firm Value: Sustainability, Risk Business, Dividend Policy, Capital Structure, and Profitability in Telecommunication - Aditya Sabrian Amirullah; Pardomuan Sihombing (ARE Publisher, 2026)
Objectives: To examine the effects of ESG disclosure, business risk (DOL), dividend policy (DPR), and capital structure (DER) on firm value (PBV), with profitability (ROE) as a mediating variable, in telecommunications companies listed on the Indonesia Stock Exchange. Methodology: The research employs a Quantitative explanatory research using balanced panel data (2020–2024). Data from 9 telecommunications companies were analyzed using panel data regression with the Random Effect Model, complemented by the Sobel test for mediation. Findings: The results indicate that ESG disclosure negatively affects firm value, business risk has a weak positive effect, dividend policy negatively affects firm value, and capital structure positively influences firm value. Profitability significantly increases firm value and mediates only the effect of capital structure. Conclusion: The study concludes that firm value in Indonesia’s telecommunications sector is primarily driven by capital structure and profitability. ESG initiatives and dividend payout decisions do not enhance valuation unless aligned with growth and financial performance.